Territorial cohesion trends in Inner Scandinavia - Medeiros, Eduardo (2017)
The article examines whether the goal of territorial cohesion can be achieved in the area designated ‘Inner Scandinavia’ through the interventions of the European Union’s cross-border cooperation programme, INTERREG-A. The programme supports a polycentric development of the Inner Scandinavian border region, which is one of three Swedish-Norwegian INTERREG-A sub-programmes. Since 1994 substantial progress has been made in the Swedish-Norwegian INTERREG-A programme, which recently ended its third generation (2007–2013), with the overarching goals of strengthening the attractiveness and competitiveness of the border region. Progress can be witnessed in the improved selectivity of the projects, which have become fewer, with more funding and more focus on innovation, and of the involved partners, with increasing participation by universities and research centres. However, despite the maturity of the Nordic crossborder programme, many challenges lie ahead. In general, the Swedish-Norwegian border region continues to lag behind in the Scandinavian socio-economic context, in which the main urban agglomerations (Stockholm, Oslo, and Gothenburg) benefit from competitive territorial advantages such as human capital, knowledge centres, decision-making structures, access to capital, and accessibility.